2022
DOI: 10.1111/tpj.15649
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Dε interacts with autophagy‐related protein 8 and promotes autophagy in Arabidopsis response to nitrogen deficiency

Abstract: SUMMARY Autophagy delivers cellular cargoes for degradation and plays an important role in nutrient recycling under nutrient limitation. A critical component in autophagy is the lipidation of phosphatidylethanolamine (PE) to autophagy‐related protein 8 (ATG8) to form ATG8‐PE. Here we show that phospholipase Dε (PLDε) in Arabidopsis cells interacts with ATG8 and hydrolyzes ATG8‐PE conjugates. In response to nitrogen deficiency, the transcript and protein levels of PLDε increase and additionally, an increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
(171 reference statements)
0
11
0
Order By: Relevance
“…Among 12 PLDs in Arabidopsis, only PLDε was found to be involved in N deficiency response (Hong et al, 2009), and its expression increased in response to N deficiency (Yao et al, 2022). In this study, the expression of soybean PLDε1 and PLDε2 was induced by nitrogen starvation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Among 12 PLDs in Arabidopsis, only PLDε was found to be involved in N deficiency response (Hong et al, 2009), and its expression increased in response to N deficiency (Yao et al, 2022). In this study, the expression of soybean PLDε1 and PLDε2 was induced by nitrogen starvation.…”
Section: Discussionmentioning
confidence: 55%
“…Particularly, overexpression (OE) of PLDε enhanced growth under N deficiency in Arabidopsis (Hong et al, 2009) and canola (Lu et al, 2016). Our recent results indicate that one mechanism by which PLDε enhances Arabidopsis growth is via its interaction with and promotion of autophagy to promote N recycling (Yao et al, 2022). Thus, PLDε could be one target for enhancing plant growth under limited N conditions.…”
Section: Introductionmentioning
confidence: 91%
“…For example, under nutrient limitation, cells induce autophagy that delivers cellular cargoes for degradation as a part of the nutrient recycling mechanism. The role of PA in plant autophagy could be inferred from data on plant [ 145 ] and animal [ 146 ] systems. In Arabidopsis , At PLDε has been found to promote autophagy in plant response to nitrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological analysis indicates that At PLDε acts to delay senescence in response to nitrogen deficiency. The transcript level of At PLDε was increased in these stress conditions, while analysis of At PLDε-GFP cellular distribution indicated that nitrate starvation increased protein levels of At PLDε [ 145 ] and promoted its association with intracellular membranes. Co-immunoprecipitation and bimolecular fluorescence complementation analysis indicate that At PLDε interacts with At ATG8, an autophagy-related protein that is essential for the biogenesis, cargo recruitment and maturation of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation